Me : britannica discovery library - Dell, Pamela; Terracciano, Kezia (Encyclopaedia Britannica, Inc. Chicago, 2005)
This book invites readers to explore the concept of self-identity, encouraging introspection and personal growth. Through engaging narratives and activities, it helps individuals understand their unique traits and perspectives.